Reducing the income tax burden for households with children: An assessment of the child tax credit reform in Austria - Michael Christl; Silvia De Poli; Janos Varga (University of Essex, Institute for Social and Economic Research (ISER), 2020)
This paper analyses the impact of the implementation of a child tax credit in Austria in 2019, both on micro and macro level. First, we assess the fiscal and distributional impact of this reform using EUROMOD. Second, we estimate labour supply impacts of the reform based on a structural discrete choice framework. Third, we evaluate the macroeconomic impacts, by calibrating and shocking the DSGE model QUEST, with the micro-based results. We show that the reform reduces inequality, lowers the poverty rate for households with children. Overall the reform has a positive impact on labour supply, especially for women. On the macro-level (and in the long-run), our model suggests a small but positive impact on employment, investment, consumption and GDP. Additionally, using the macro impact of the reform, we show that accounting for those behavioural responses at the micro level is important to asses the long-run impact of tax reforms, especially on the income distribution.
Keywords: H24; H31; I38; 330; EUROMOD; tax credit; reform; DSGE; labour supply; microsimulation